On the approaches applied in formulation of a kinetic model of photosystem II: Different approaches lead to different simulations of the chlorophyll alpha fluorescence transients - Lazár, Dusan; Jablonský, Jirí (Journal of theoretical biology, 2009)
Chlorophyll a fluorescence rise (O-J-I-P transient) was in literature simulated using models describing reactions occurring solely in photosystem II (PSII) and plastoquinone (PQ) pool as well as using complex models which described, in addition to the above, also subsequent electron transport occurring beyond the PQ pool. However, there is no consistency in general approach how to formulate a kinetic model and how to describe particular reactions occurring even in PSII only. In this work, simple kinetic PSII models are considered always with the same electron carriers and same type of reactions but some reactions are approached in different ways: oxygen evolving complex is considered bound to PSII or "virtually" separated from PSII; exchange of doubly reduced secondary quinone PSII electron acceptor, Q(B), with PQ molecule from the PQ pool is described by one second order reaction or by two subsequent reactions; and all possible reactions or only those which follow in logical order are considered. By combining all these approaches, eight PSII models are formulated which are used for simulations of the chlorophyll a fluorescence transients. It is shown that the different approaches can lead to qualitatively different results. The approaches are compared with other models found elsewhere in the literature and therefore this work can help the readers to better understand the other models and their results.
Keywords: biologické modely; Models, Biological; Photosystem II Protein Complex; rostliny; Chlorophyll A; Plants; chlorofyl; Photochemistry; Photosynthesis; fotosystém II (proteinový komplex); fluorescence; fotochemie; Computer Simulation; Fluorescence; chlorofyl a; Chlorophyll; fotosyntéza; počítačová simulace